Topology optimization of plate structures using plate element-based moving morphable component (MMC) approach - Cui, Tianchen; Sun, Zhi; Liu, Chang; Li, Linyuan; Cui, Ronghua; Guo, Xu (Acta mechanica Sinica, 2020)
A topology optimization approach for designing the layout of plate structures is proposed in this article. In this approach, structural mechanical behavior is analyzed under the framework of Kirchhoff plate theory, and structural topology is described explicitly by a set of moving morphable components. Compared to the existing treatments where structural topology is generally described in an implicit manner, the adopted explicit geometry/layout description has demonstrated its advantages on several aspects. Firstly, the number of design variables is reduced substantially. Secondly, the obtained optimized designs are pure black-and-white and contain no gray regions. Besides, numerical experiments show that the use of Kirchhoff plate element helps save 95–99% computational time, compared with traditional treatments where solid elements are used for finite element analysis. Moreover the accuracy of the proposed method is also validated through a comparison with the corresponding theoretical solutions. Several numerical examples are also provided to demonstrate the effectiveness of the proposed approach.